The Evolvement of Constructionism: An Overview of the Literature - Zaphiris, Panayiotis; Parmaxi, Antigoni (My University, 2014)
This paper reviews the theory of constructionism from its evolvement in 1980s towards its more recent implementations. By reviewing recent research conducted under the framework of constructionism, we set off in understanding its key ideas and their evolution over time. At the same time this paper acknowledges obstacles, challenges and critiques towards implementing constructionism in the teaching and learning practice. The paper is organized around three sections: constructionism, distributed constructionism and social constructionism. The findings of this study reveal the dynamic progression of constructionism and its potential to be used as a pervasive theoretical framework for instructional technology in various settings.
Keywords: theory of learning; Papert; Logo; microworlds construction; artifact; object-to-think-with; social technologies